The taxonomy key for Mugilidae in Vietnam - Viet Thanh, Tran Thi; Long, Phan Ke; Deivasisamani, B. (Academia Journal of Biology, 2015)
In Vietnam, the Mugilidae is comprised of 5 genus, 22 species. More than 700 specimens belonging to 8 genus, 17 species of Mugilidae were analysed using morphological characters and CO1 sequences. The results showed that the Mugilidae is very popular in Vietnam but they are very difficult distingushed from each other because their morphological characters are not clear. However some characters such as preorbital, maxilla, adipose eyefold, head structure, caudal fin and anal fin rays can be use for distingused the genus Mugil, Valamugil and Liza. We also provide a taxonomy key for indentifying the species in the Mugilidae in Viet Nam.